Perancangan Interior Kafe Dharmawangsa Hotel Singgasana di Surabaya - Diyanto, Meichael Ferderrick; Indrani, Hedy Constancia; Nilasari, Poppy Firtatwentyna (Intra, 2019)
Human in general have a close relationship with nature, but within the current era development, they begin to part away from nature. Human will feel peaceful when in a nature themed room, because the nature atmosphere that’s quiet so that people are comfortable when in it. A place that is often used by humans or people in order to relax in general is a café, where people can gather, relax and rest. Surabaya is a big city that has vast population, so Surabaya needs a lot of cafes that can be placed in various locations. A nature-themed café is a solution that can be offered to public as a place to relax when they have finished their work. The café provides an intense atmosphere with nature, so that human’s relationship with nature can restored.